Kecemasan Berdampak kepada Keteraturan Siklus Menstruasi pada Remaja Putri - Sundari, Sundari; Arwiyantasari, Wida Rahma; Ardhianingtyas, Nisa (FORUM ILMIAH KESEHATAN, 2023)
In general, the menstrual cycle lasts about five days. The occurrence of menstruation is influenced by the hormonal system and it is also possible that someone who experiences menstruation has psychological problems. This study aimed to determine the relationship between the anxiety level of adolescent girls and the regularity of the menstrual cycle. This research was carried out using a cross-sectional design. This research involved 53 adolescent girls who were chosen randomly. Data on anxiety levels were collected through the HARS questionnaire, while data on menstrual regularity were also obtained through interviews. The correlation between the two variables was analyzed using the Chi-Square test. The results showed that the majority of adolescent girls experienced anxiety (51%); and the majority of them experience irregular menstrual cycles (88.9%). The results of the analysis for hypothesis testing showed a p value = 0.000 or there was a significant correlation between anxiety levels and the regularity of the menstrual cycle. Furthermore, it was concluded that the level of anxiety had an impact on the regularity of the menstrual cycle in adolescent girls.Keywords: anxiety level; menstrual cycle; adolescent girls ABSTRAK Pada umumnya, siklus menstruasi berlangsung selama sekitar lima hari. Terjadinya menstruasi dipengaruhi oleh sistem hormonal dan tidak menutup kemungkinan juga seseorang yang mengalami menstruasi mempunyai masalah psikologis. Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat kecemasan remaja putri dengan keteraturan siklus menstruasi. Penelitian ini dilaksanakan dengan menerapkan rancangan cross-sectional. Penelitian ini melibatkan 53 remaja putri yang dipilih secara random. Data tentang tingkat kecemasan dikumpulkan melalui kuesioner HARS, sedangkan data tentang keteraturan menstruasi juga diperoleh melalui wawancara. Korelasi antara kedua variabel dianalisis menggunakan uji Chi-Square. Hasil penelitian menunjukkan bahwa mayoritas remaja putri mengalami kecemasan (51%); dan mayoritas dari mereka mengalami siklus mestruasi yang tidak teratur (88,9%). Hasil analisis untuk pengujian hipotesis menunjukkan nilai p = 0,000 atau ada korelasi secara signifikan antara tingkat kecemasan dengan keteraturan siklus menstruasi. Selanjutnya disimpulkan bahwa tingkat kecemasan berdampak kepada keteraturan siklus menstruasi pada remaja putri. Kata kunci: tingkat kecemasan; siklus menstruasi; remaja putri